Kenyan dominance in distance running - Larsen, H. B. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2003)
Critical physiological factors for performance in running are maximal oxygen consumption (VO2max), fractional utilization and running economy. While Kenyan and Caucasian elite runners are able to reach very high, but similar maximal oxygen uptake levels, the of black South African elite runners seems to be slightly lower. Moreover, the studies of black and white South African runners indicate that the former are able to sustain the highest fraction of VO2max during long distance running. Results on adolescent Kenyan and Caucasian boys show that these boys are running at a similar percentage of during competition. Kenyan elite runners, however, appear to be able to run at a high % of VO2max which must then have been achieved by training. A lower energy cost of running has been demonstrated in Kenyan elite runners and in untrained adolescent Kenyan boys compared to their Caucasian counterparts. In agreement with this are the results from studies on black South African elite runners who have shown similar low energy costs during running as the Kenyan elite runners. The good running economy cannot be explained by differences in muscle fibre type as they are the same in Kenyan and Caucasian runners. The same is true when comparing untrained adolescent Kenyan boys with their Caucasian counterparts. A difference exists in BMI and body shape, and the Kenyans long, slender legs could be advantageous when running as the energy cost when running is a function of leg mass. Studies comparing the response to training of Kenyans and Caucasians have shown similar trainability with respect to VO2max, running economy and oxidative enzymes. Taken all these data together it appears that running at a high fractional VO2max and having a good running economy may be the primary factors favouring the good performance of endurance athletes rather than them having a higher VO2max than other elite runners. In addition to having the proper genes to shape their bodies and thereby contributing to a good running economy, the Kenyan elite runners have trained effectively and used their potential to be in the upper range both in regard to VO2max and to a high utilization of this capacity during endurance running.